Epichloë hybrida, sp. nov., an emerging model system for investigating fungal allopolyploidy. (3rd September 2017) - Campbell, Matthew A.; Tapper, Brian A.; Simpson, Wayne R.; Johnson, Richard D.; Mace, Wade; Ram, Arvina; Lukito, Yonathan; Dupont, Pierre-Yves; Johnson, Linda J.; Scott, D. Barry; Ganley, Austen R. D.; Cox, Murray P.
ABSTRACT: Endophytes of the genus Epichloë (Clavicipitaceae, Ascomycota) frequently occur within cool-season grasses and form interactions with their hosts that range from mutualistic to antagonistic. Many Epichloë species have arisen via interspecific hybridization, resulting in species with two or three subgenomes that retain all or nearly all of their original parental genomes, a process termed allopolyploidization. Here, we characterize Epichloë hybrida, sp. nov., a mutualistic species that has increasingly become a model system for investigating allopolyploidy in fungi. The Epichloë species so far identified as the closest known relatives of the two progenitors of E. hybrida are E. festucae var. lolii and E. typhina . We confirm that the nuclear genome of E. hybrida contains two homeologs of most protein-coding genes from E. festucae and E. typhina, with genome-wide gene expression analysis indicating a slight bias in overall gene expression from the E. typhina subgenome. Mitochondrial DNA is detectable only from E. festucae, whereas ribosomal DNA is detectable only from E. typhina . Inheriting ribosomal DNA from just one parent might be expected to preferentially favor interactions with ribosomal proteins from the same parent, but we find that ribosomal protein genes from both parental subgenomes are nearly all expressed equally in E. hybrida . Finally, we provide a comprehensive set of resources for this model system that are intended to facilitate further study of fungal hybridization by other researchers.